The impact of digital technologies in nursing care and their application: A narrative review - Narges Toghian Chaharsoughi; Mansoureh Ahmadifaraz; Leila Sadat Kahangi (Shahrekord University of Medical Sciences, 2022)
Background and aims: Digital technologies promise great opportunities to overcome current challenges in the care sector. Examples include the growing presence of robotic systems and society's reliance on mobile, the internet, and social media. Despite substantial advances, challenges in the nursing use of digital technology persist. A lack of good empirical reviews of current technologies in the literature prompted us to conduct this review. Methods: This study was conducted using a narrative review method. We reviewed studies published from 2010 to 2022. Data were collected by searching different English and Persian databases, namely, Google Scholar, Elsevier, PubMed, ProQuest, and Scientific Information D atabase (SID). Search terms were "digital technology," "social media," "monitoring technologies," "eHealth services," "nursing care," "digital technology application," and "innovative technology." Results: Evidence shows that digital technology in the field of nursing care is classified into three types (types of digital technology in nursing, advantages and disadvantages of digital technology, and challenges and attitudes of nurses in the use of digital technology in nursing care). Each dimension was examined separately. This study uses digital technology in nursing care: Information and communication technology (ICT), ambient assisted living, assistive devices, monitoring/sensors, robotic technology, and virtual reality. Conclusion: Despite substantial advances, digital technology challenges persist in nursing use. Nurses must catch up with rapid changes in digital technologies and their impact on society, limiting their potential benefits to nursing practice and patient care. To respond to these challenges and prepare for the future, nursing must begin the immediate transformation into a digitally enabled profession that can respond to the complex global challenges facing health systems and society.